Flaw recognition in reinforced concrete bridges using infrared thermography: A case study - Joaquin Humberto Aquino-Rocha; Yêda Vieira Póvoas; Pedro Igor Bezerra-Batista (Revista Facultad de Ingeniería Universidad de Antioquia, 2023)
Infrared thermography is a non-destructive test that is increasingly used in the inspection of existing buildings, bridges, and civil works. However, its practice is limited due to the influence of environmental conditions on the results of the test. The present study aims to evaluate the methodology of the test through the inspection of existing reinforced concrete bridges in Recife, Brazil. This city presents different environmental conditions from those reported in the literature, a high ambient temperature and relative humidity. The study comprises the inspection of five bridges in two days, analyzing their superstructure and infrastructure separately. The results show that flaw recognition is possible through the temperature gradient between imperfect and intact regions. Thus, variation in temperature greater than 0.3 °C allows awareness of the problem. The results behavior is different based on the bridge section inspected. The defects in the bridge superstructure are presented as positive thermal gradients. On the other hand, bridge infrastructure’s deficiencies are shown as negative thermal gradients. Although the technique presents several advantages for the inspection, the results must be analyzed in detail to avoid false detections, which may compromise the correct diagnosis of the bridge structures.